IDENTIFIKASI KESALAHAN SISWA DALAM MENYELESAIKAN SOAL FUNGSI KUADRAT DI KELAS X SMAN 1 PALANGKA RAYA - Siti Karsini; Sugiharto; Janu Pinardi (JURNAL PENDIDIKAN, 2024)
This research is based on an interview with a mathematics teacher of class X SMAN 1 Palangka Raya. Errors in solving the problems are caused by students having difficulty understanding and determining the formula used. At school, there has never been an identification of errors and causes of student errors in solving the quadratic function problems. The purpose of the research is to identify and describe the types of errors and the causes of students making mistakes in solving the quadratic function problems. This research is descriptive research with a qualitative approach. The research was conducted in the even semester of the 2023/2024 school year. The research subjects consisted of 42 students. Tests and interviews are data collection techniques used. After the test, three students were selected to be interviewed to find the causes of errors.  The results concluded that the types of errors made by students in solving quadratic function problems are: (1) Conceptual errors, students forget to write signs in parentheses when describing the square, incorrectly determine the formula used, and lack of student understanding of the quadratic function material. (2) Procedural errors, students are not correct in the steps when solving the problem or the completion steps are incomplete. (3) Technical errors, students are wrong in calculating the value of mathematical operations and students' inaccuracy in mathematical operations. The causes of students making mistakes are: (1) Knowledge, because students forget, and also the lack of student knowledge of the quadratic function material. (2) Understanding, most students lack understanding and lack of understanding of the quadratic function material. (3) Application, students are not precise in their solution steps.